A long-lasting gel-based diffuser of feline pheromone can help reduce undesirable behaviors in cats at home: comparison with an electric diffuser - Espuña, Gemma; Nicolas, Céline S.; Girardin, Aurélie; Fatjó, Jaume; Bowen, Jonathan; Monginoux, Patricia; Rème, Christophe A. (Frontiers in Veterinary Science, 2024)
Using pheromone diffusers is part of the strategy to control stress-related behaviors in cats (Felis catus). The goal of the study was to compare the efficacy of a novel long-acting, unpowered gel-based diffuser containing a facial pheromone analog (Zenifel® gel diffuser, Virbac) with a similar electrically powered feline pheromone diffuser that already has proven efficacy, on situational stress in cats, at home. The study involved ninety owners of cats presenting undesirable behaviors receiving one diffuser or the other: forty-six received one gel diffuser and forty-four received one plug-in device and a refill, for the two-month study duration. The presence of the various undesirable behaviors was checked regularly and a general score was given to rate their presence. The most reported behaviors were related to hypervigilance, seeking the owner's attention, hiding, excessive vocalization, inactivity, and excessive scratching. All six behaviors significantly improved over time with Zenifel® while only four improved with the reference product (no improvement for excessive meowing and inactivity). The general score significantly improved as of day 7 in both groups, with no difference between groups. More owners said they would use the product throughout the year with Zenifel® than with the reference product (80% vs. 42%, p<0.05). Therefore, both diffusers can be used to help control undesirable behaviors of cats at home but Zenifel® is more convenient to use throughout the year.